Does preoperative tamsulosin facilitate semirigid ureteroscopic management of lower ureteric calculi? A prospective, randomized double-blind study - Ahmed A. Shahat; Ahmad A. Elderwy; Mahmoud A. Gaber; Nasreldin Mohammed (Current Urology)
Abstract. Background. The use of tamsulosin before semirigid ureteroscopy (URS) for proximal ureteral stones increases operative success. Several authors have used α-blockers for dilation of the ureter, and most studies have observed a higher stone-free rate and fewer complications than those with a placebo or no use of drugs. Ureteroscopy is the standard treatment for ureteral stones and has excellent outcomes. This study aimed to assess the effect of preoperative tamsulosin on the intraoperative and postoperative outcomes of URS in the management of lower ureteric stones. Materials and methods. This was a double-blind randomized placebo-controlled clinical trial. A total of 80 patients were included, 40 in each group. The closed envelope method of randomization was performed at the Assiut Urology and Nephrology Hospital (Urology Department), Faculty of Medicine, Assiut University, Egypt, from December 2019 to November 2021. Results. Both groups showed no significant differences in age, and the majority of patients in both groups were male. Most patients had a moderate degree of obstruction, and the stones were radiopaque. Both groups showed insignificant differences in stone size (11.93 ± 3.39 vs. 12.40 ± 4.24 mm, p = 0.30). Operative time was significantly shorter in the study group than in the control group (61.50 ± 23.99 vs. 79.80 ± 23.22 minutes, p = 0.001). The control group had a significantly higher frequency of need for dilatation (80% vs. 20%, p < 0.001) and need to stent than the study group (60% vs. 22.5%, p = 0.001). Conclusions. Preoperative tamsulosin facilitates URS for lower ureteric stones. It decreases operative time, the need for dilation, and the need for postoperative indwelling ureteral stenting. It also increases the success rate but does not significantly affect the complication rate.